ANALISIS STRAREGI MEMPERTAHANKAN KEARIFAN LOKAL TANAMAN GAMBIR DI DESA MANGGILANGKECAMATAN PANGKALAN KOTO BARU KABUPATEN LIMA PULUH KOTA - Yansyah, Sepri; Sayamar, Eri; Kausar, Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aimedtoidentifylocal wisdomis ever existed gambierplant(from past done butdid notdoit present), which isstillcarried outand thegambierfarmerswhowere past and the present  do,  and whichwere notpast donebutpresent do of gambier farmers. This research usessurveyandSnowball Samplingmethodin findingthe properrespondentto obtain the14respondents consistingof1) FarmersGambier, 2) NinikMamak, 3) Religious Leaders, 4) ApparatusVillage. Methodsinterviews were conductedtoobtaininformationaboutlocal wisdomgambierplants. Descriptive and qualitative analysisin preparingthis research. Criteriathatrespondentswhosoughtgambierfarmerswhohavelongexperienceand thecultivation oflocal wisdomto knowthe gambierplant.while for answer the purpose to three that is strategy for maintain the local wisdom analyzed by using SWOT analysis. The results showedthatlocal wisdom of gambierplant in the village Manggilang districts Pangkalan Koto Baru totaling 45 local wisdom from past done or present do of gambier farmers. 1). Local wisdom from past done butdid notdoit present totaling 5 local wisdom. 2). Local wisdom from past done and now present  do totaling 40 local wisdom. 3). Strategy for maintain the local wisdom is attractiveness to traveler the need for role of government and use tools traditional relatively cheap and easy to get by farmers.Keywords:Local Wisdom, Gambier Plant, Gambier Farmers, Past, Present